Assessing Enteric Methane Emissions in Ruminants: A Comparative Study of the Green Feed Technique - Vaidya, Mangesh; Patodkar, V. R.; Kuralkar, Prajakta; Amrutkar, Suhas; Panchbhai, Girish; Gupta, Mahesh; Kapale, Prashant; Singh, S. V. (International Journal of Bio-resource and Stress Management, 2025)
Livestock-generated methane, particularly from cattle, was a significant contributor to climate change. Methane emissions from ruminant animals, such as cows and sheep, are primarily caused by the microbial fermentation of food in their digestive systems, a process known as enteric fermentation by making this process a prime source of greenhouse gas emissions in animal production. Considerable knowledge gaps existed in animal agriculture regarding effective strategies for mitigating these emissions while maintaining productivity. A key factor was the uncertainty surrounding methods for estimating emission rates, each having inherent limitations. For example, the suitability of the GreenFeed system varied based on specific experiment objectives. Compared to respiration chambers and the sulfur hexafluoride tracer method, the The GreenFeed system often required more time and a larger number of animals for treatment comparisons due to higher within-day variances. It measured numerous short-term methane emissions from individual animals at various times throughout the day over several days. Recent advancements focused on improving accuracy, ease of use, and cost-effectiveness, essential for better monitoring of greenhouse gases. Traditional methods, such as respiration chambers, while accurate, were costly and impractical for field measurements. The GreenFeed system’s software facilitated control over feed availability timing and CH4 measurement allocation. Therefore, careful planning was necessary to ensure accurate estimates of methane production. This review emphasized the need for effective measurement techniques to mitigate methane emissions from livestock.